A Review of Juridical and Criminological The Crime of Horrible Bodily Damage - Muh. Iqbal Ameth; Hamsir; Natsif, Fadli Andi (Department of Law, Universitas Islam Negeri Alauddin Makassar, 2024)
This study aims to examine the application of material criminal law related to the crime of grievous bodily harm and the consideration of judges in determining criminal sanctions against perpetrators. Conducted in the Makassar District Court with a qualitative approach using the interview method. The results showed that the panel of judges in certain cases found the defendant guilty in accordance with Article 351 of the Criminal Code, based on the facts of the trial such as witness statements and evidence. Although the judge's decision tends to judicial considerations without specifying the background of the subjective consideration, the sanctions imposed are in accordance with the law, although they are lower than the prosecutor's demands.